Edukasi dan Sosialisasi Manajemen Kinerja Pada Unit Karir Alumni dan Pengembangan Pada Universitas Bina Darma - Anugrah Ilham Fareza; Dina Melita (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The management of alumni data and the implementation of tracer studies are essential components in supporting the improvement of higher education service quality. The Career, Alumni, and Student Development Unit of Bina Darma University plays a strategic role in managing alumni information and providing the necessary data for graduate evaluation and educational program development. The problems faced include the suboptimal updating of alumni data and alumni participation in tracer study activities. This community service activity aims to provide assistance in alumni data management and optimize the implementation of tracer studies to enhance the unit's service effectiveness. The methods employed include observation, administrative assistance, socialization on the importance of tracer studies, and evaluation of activity outcomes. The results indicate an increase in staff understanding of alumni data management, improved coordination in tracer study implementation, and enhanced effectiveness of the alumni data collection process. This activity provides a positive contribution in supporting the improvement of service quality for the Career, Alumni, and Student Development Unit of Bina Darma University.